'Building a Ship while Sailing It.' Epistemic Humility and the Temporality of Non-knowledge in Political Decision-making on COVID-19. (4th May 2021) - Parviainen, Jaana; Koski, Anne; Torkkola, Sinikka
ABSTRACT: The novel coronavirus pandemic (COVID-19) has had far-reaching effects on public health around the world. Attempts to prevent the spread of the disease by quarantine have led to large-scale global socioeconomic disruption. During the outbreak, public authorities and politicians have struggled with how to manage widespread ignorance regarding the virus. Drawing on insights from social epistemology and the emerging interdisciplinary field of ignorance studies, this article provides evidence that the temporality of non-knowing and its intersection with knowing is a force that leads political decision-making during a crisis. Illuminating the epistemic analysis with statements given by the Finnish government to the media in decision-making documents and in press conferences, this paper proposes that a crisis situation, itself, seems to demand from political decision-makers dynamic action while simultaneously knowing little ('non-knowing') about the different fronts of tackling the pandemic. We conclude that non-knowing must be recognized explicitly as an enduring and central condition in decision-making, which we call 'epistemic humility.'